2006
DOI: 10.1007/s10265-005-0256-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ABA upon anthocyanin synthesis in regenerated torenia shoots

Abstract: To elucidate the mechanism of anthocyanin synthesis induction concomitant with chlorophyll degradation, we established a system in which anthocyanin synthesis and degradation of chlorophyll in regenerated torenia (Torenia fournieri) shoots was induced on medium containing 7% sucrose. Here, we studied the effect of several plant-growth regulators on anthocyanin synthesis and the degradation of chlorophyll in the torenia shoot regenerating system. Exogenous abscisic acid (ABA) could induce anthocyanin synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
1
36
1
1
Order By: Relevance
“…Furthermore, Fambrini et al (1993) have demonstrated, using a Helianthus annuus mutant plant deficient in ABA biosynthesis, that ABA accumulation is necessary for the induction of anthocyanin biosynthesis. In another study, Nagira et al (2006) induced osmotic stress in Torenia plants with sucrose (Table 2). They determined that under osmotic stress endogenous ABA levels rise significantly before the induction of anthocyanin synthesis.…”
Section: Induction Mechanism Under Drought Stressmentioning
confidence: 87%
“…Furthermore, Fambrini et al (1993) have demonstrated, using a Helianthus annuus mutant plant deficient in ABA biosynthesis, that ABA accumulation is necessary for the induction of anthocyanin biosynthesis. In another study, Nagira et al (2006) induced osmotic stress in Torenia plants with sucrose (Table 2). They determined that under osmotic stress endogenous ABA levels rise significantly before the induction of anthocyanin synthesis.…”
Section: Induction Mechanism Under Drought Stressmentioning
confidence: 87%
“…In addition, one recent report suggests that lemon balm leaves were exposed to high levels of sucrose, and in response, the anthocyanins and flavonoids accumulated (Hossain et al, 2009). Sugarinduced anthocyanin accumulation has been reported in other plant species (Nagira et al, 2006;Solfanelli et al, 2006). The accumulation of total polyphenol, flavonoid, and antho cyanin contents in CCC-treated ginkgo leaves might also has a few relationships with the extra soluble sugar content, which was enhanced by CCC treatment.…”
Section: Effect Of CCC On Total Polyphenols Flavonoids and Anthocyaninsmentioning
confidence: 81%
“…ABA increases the activity of PAL, a key regulatory enzyme of anthocyanin biosynthesis, and promotes senescence of rice leaves (Hung & Kao 2004). Exogenous ABA induced anthocyanin synthesis in regenerating Torenia fournieri shoots in the medium containing a low concentration of sucrose (1.5%) (Nagira et al 2006). Application of ABA (at 0.01 to 1 µM) to non-chlorophyllous corn leaf segments had a stimulatory effect on anthocyanin accumulation.…”
Section: Abscisic Acidmentioning
confidence: 99%
“…The synthesis of anthocyanins is also suggested to be under hormonal control (Weiss et al 1995, Peng et al 2011, Nagira et al 2006.…”
Section: Introductionmentioning
confidence: 99%